Evaluation of the Suitability of Al-Badaa River Water, North of Dhi-Qar Governorate, for Multi-Purpose Uses - Chlaib, Hussein Kh.; Toban, Mohammed O.; Abbas, Isam Kareem; Zachi , Hakeem R (University of Thi-Qar Journal of agricultural research, 2025)
Abstract: Al-Badaa River was chosen for the study as the main source of drinking water in the city of Al-Shatrah and the surrounding areas. Al-Badaa River water was studied when it entered Shatrah district. Three replicates were taken from the river water from the southern side of Al-Badaa Dam on 12/14/2022. Some physical and chemical properties (pH, Total Dissolved Salts (TDS), Calcium (Ca), Carbonate (CO3), Bicarbonate (HCO3), Turbidity (TUR), Electrical Conductivity (EC), Chlorine (Cl)) were measured. The pH value was 8.622, EC was 1080 meq/cm, TDS was 705 ppm, Cl was 17 meq/l, HCO3 was 3.5 meq/l, and Ca value was 6.3 meq/l. The turbidity value was 36.42 FTU. Comparing the results with WHO specification shows that the levels of all studied properties did not exceed the permissible limits according to those specifications. Also, it was found that Al-Badaa River water is suitable for human use. In order to show the suitability of Al-Badaa River water for animal husbandry purposes, the obtained values were compared with international standard specifications for public USA veterinary services, the studied water quality was found to be very good for animal husbandry purposes and is excellent quality for irrigation.